(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In the information-driven world of today, the ability to read and write is not just a skill, it is a lifeline. Yet, millions of people, especially women, still lack this basic human right. Despite the rise of digital tools and informal learning, formal education remains the most reliable path to ending illiteracy. This paper explores what illiteracy truly means and why formal education; structured, inclusive, and teacher-led continues to matter. From ancient civilizations to modern classrooms, formal education has served as society’s most effective system for teaching literacy. It provides a structured environment, ensures equal access, and nurtures not just reading and writing, but also critical thinking, empathy, and community belonging. While digital learning can enhance education, it cannot replace the human connection and accountability that formal schooling offers. To end illiteracy, we must reform and not replace formal education by investing in teacher training, modern curricula, and equitable access. Literacy opens doors to opportunity, dignity, and development. The key to that door is still held by our schools.